Performativity Double Standards and the Sexual Orientation Climate at a Southern Liberal Arts University. Issue 5 (16th April 2017) - Byron, Reginald A.; Lowe, Maria R.; Billingsley, Brianna; Tuttle, Nathan
ABSTRACT: This study employs quantitative and qualitative methods to examine how heterosexual, bisexual, and gay students rate and describe a Southern, religiously affiliated university's sexual orientation climate. Using qualitative data, queer theory, and the concept tyranny of sexualized spaces, we explain why non-heterosexual students have more negative perceptions of the university climate than heterosexual male students, in both bivariate and multivariate analyses. Although heterosexual students see few problems with the campus sexual orientation climate, bisexual men and women describe being challenged on the authenticity of their orientation, and lesbian and, to a greater extent, gay male students report harassment and exclusion in a number of settings. These distinct processes are influenced by broader heteronormative standards. We also shed much-needed light on how gendered sexual performativity double standards within an important campus microclimate (fraternity parties) contribute to creating a tyrannical sexualized space and negatively affect overall campus climate perceptions.